Influence of platelet content on the fabrication of colloidal gels for robocasting: Experimental analysis and numerical simulation. Issue 3 (March 2020) - Lorenz, Mylena; Dietemann, Bastien; Wahl, Larissa; Bierwisch, Claas; Kraft, Torsten; Kruggel-Emden, Harald; Travitzky, Nahum
Abstract: The preparation of colloidal gels containing different amounts of platelet and sphere-like powders is presented for the production of textured structures using robocasting and templated grain growth methods. The influence of platelet amount on paste fabrication and extrusion is investigated experimentally and numerically. Rheology of the pastes showed the need to vary coagulant and total filling fraction to obtain a paste suitable for robocasting. Pastes containing up to 0.15 platelet fractions were successfully extruded through 0.5 mm and 1.5 mm nozzle diameters. Pastes with platelet content higher than 0.18 and different filling fractions could only be extruded through the 1.5 mm nozzle. Discrete Element Method simulation predicts that the extrusion of pastes containing a high amount of platelets through a thinner nozzle was not possible due to powder morphology and size. Thus, the simulation supports the assumption that a high amount of platelets might be unprintable using thinner nozzles.